Pemodelan Estimasi Kerusakan Jalan Metode Markov - Rindah Intansari Mukti; Ludfi Djakfar; M. Zainul Arifin (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Roads with damaged conditions can cause traffic accidents and hinder society's economic and social progress. Roads that are left hurt and no repairs will further worsen the condition of these roads. For this reason, it is necessary to analyze the modeling of estimated road damage, which is needed to get an informed picture of future road pavement changes. This study aims to predict road conditions for five years, with the research location being on six roads in Malang Regency. This research method uses interviews and secondary data collection using Markov chain analysis. The method used in this study is the Markov Chain method, which is a method that studies the properties of a variable in the present based on its past properties to determine the properties of these variables in the future. The results of modeling road damage are when road repairs are not carried out, and the injury worsens yearly. On the roads studied, road damage increased from year 0 to year 1, and there were many increases ranging from 2% -7%, and for years 1 to 5, there was an increase of 1%. The conclusion of this study is that road damage is increasing because there is no repair at all, so more funds are needed for road repair costs.